Antioxidant Activities of Ginger (Zingiber officinale) and Telang Flower (Clitoria ternatea L.) Combination Tea - Wahyu Widowati; Teresa Liliana Wargasetia; Teddy Marcus Zakaria; Meganita Marthania; Michael Sebastian Gunadi; Nathanael Halim; Nindia Salsabila Mia Dewi; Sherly Santiadi (Majalah Kedokteran Bandung, 2022)
Tea is widely consumed for health purposes to prevent and treat various diseases. This paper reports the antioxidant activities of a herbal tea namely jahe (ginger, Zingiber officinale) telang (Clitoria ternatea L.), and the combination namely JaTe (jahe and telang). Each of jahe, telang, and JaTe teas were made of 2g ginger, 5 buds dried telang flower, and the combination respectively. The teas were boiled in 200 mL for 5 minutes. The dried ginger, telang, and JaTe formulation were evaluated for antioxidant activities. Total phenolic content was evaluated by Folin-Ciocalteu using the gallic acid equivalent (GAE), while total flavonoid content was evaluated by aluminum chloride colorimetric assay using the quercetin equivalent (QE). The antioxidant activity was measured using 2,2-diphenyl-1picrylhydrazyl (DPPH), and 2,2'-Azino-Bis-3-Ethylbenzothiazoline-6-sulfonic acid (ABTS), hydrogen peroxide (H₂O₂) scavenging activities, and ferric reducing antioxidant power (FRAP) assay. The highest phenolic and flavonoid contents were found in ginger tea with 23.62 μg GAE/100% concentration and 7.22 μg QE/100% concentration, followed by telang tea with 16.20 μg GAE/100% concentration and 4.88 μg QE/100% concentration. Ginger tea has the strongest DPPH scavenging activity with IC₅₀=7.76% followed by telang tea 17.07%. JaTe tea has the strongest ABTS scavenging activity with IC₅₀=1.01% followed by ginger tea with IC₅₀=1.26%. Ginger tea has the strongest H₂O₂ scavenging activity with IC₅₀=13.23% and followed by JaTe tea with IC₅₀=14.66%. JaTe tea has the strongest FRAP activity with IC₅₀=3.59%, followed by ginger tea with IC₅₀=4.94%. Overall, JaTe herbal tea formulation has a strong antioxidant activity.